The Brooklyn follies - Auster, Paul, 1947-; Faber and Faber (London : Faber and Faber, 2005)
Nathan Glass, a middle-aged man estranged from his friends and family, returns to Brooklyn hoping to mend his broken relationships and finally deal with the ghosts of his past.
Adult
Keywords: Autobiography -- Authorship -- Fiction; Middle-aged men -- Fiction; Retirees -- Fiction; Autobiography -- Technique -- Fiction; Domestic fiction; Psychological fiction; Brooklyn (New York, N.Y.) -- Fiction; Park Slope (New York, N.Y.) -- Fiction